Revisión bibliográfica de la aplicación de la metodología DEA en el ámbito educativo colombiano. (2013)
This article presents the results of a literature review in the national intellectual production; related to the application of the methodology of Data Envelopment Analysis (DEA; for its acronym in English) in the Colombian education. Specifically; and as of this review; the article establishes the characteristics of the objects of study of the researches and presents how the methodology is used. In conclusion; although DEA management has been increased; it is still in its infancy and therefore; there are several research opportunities that include different types of decision units (DMU); types of institutions; educational levels; coverage and study objectives.